2003
DOI: 10.1055/s-2003-38883
|View full text |Cite
|
Sign up to set email alerts
|

New Antimicrobial Alkaloids from the Roots ofPolyalthia longifoliavar.pendula

Abstract: Bioassay-guided isolation studies on the root extract of Polyalthia longifolia var. pendula possessing significant antibacterial activity led to the isolation of three new alkaloids pendulamine A (1), pendulamine B (2) and penduline (3) along with stigmasterol 3-O-beta-D-glucoside, allantoin, the known diterpenoid kolavenic acid, and the azafluorene alkaloid isoursuline. The structures of these compounds have been elucidated with the help of spectroscopic studies including 2D NMR experiments. Compounds 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 14 publications
3
57
0
1
Order By: Relevance
“…According to Murthy et al (2005) and Nair et al (2009) P.longifolia leaves are economically important because it has demonstrated significant antibacterial, antifungal, anti viral and antioxidant activities. Pharmacological studies on the bark and leaves of the plants shows display effective antimicrobial activity (Faizi et al, 2003), cytotoxic function Chen et al, 2006), hypotensive effects (Saleem et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Murthy et al (2005) and Nair et al (2009) P.longifolia leaves are economically important because it has demonstrated significant antibacterial, antifungal, anti viral and antioxidant activities. Pharmacological studies on the bark and leaves of the plants shows display effective antimicrobial activity (Faizi et al, 2003), cytotoxic function Chen et al, 2006), hypotensive effects (Saleem et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic efficacy of P.longifolia extensively used in Indian system of medicine has been established through modern testing and evaluation in different disease conditions (Katkar, 2010). Reports on the plant has shown that its various parts possess different biological activities Pharmacologic studies on the bark and leaves of this plant show effective antimicrobial activity Faizi et al, 2003), cytotoxic function Chen et al, 2006), hypotensive effects (Saleem et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Katkar et al (2010), P. longifolia performs several functions such as antibacterial, antifungal, antidiabetic, antitumor, anti-ulcer, antioxidant and used in the treatment of the digestive system. Pharmacological studies on the bark and leaves of the plants shows display effective antimicrobial activity (Faizi et al, 2003), cytotoxic function Chen et al, 2006), hypotensive effects (Saleem et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports on the presence of numerous chemical constituents with interesting biological activities. For example, alkaloids pendulamine A and B isolated from the root extract exhibited significant antibacterial activities 14 while flavonoids and their glycosides isolated from leaves possess free radical scavenging ability 15 .…”
Section: Introductionmentioning
confidence: 99%